The Validity Of Researchers Self Evaluation About Their Own Activities In Knowledge Translation(KT) - Hamid Asayesh; Mostafa Qorbani; Afsaneh Borghei; Aziz Rezapour; Younes Mohammadi; Morteza Mansourian; Fereydoon Jahahgir; Mehdi Noroozi (Tehran University of Medical Sciences, 2014)
Background and Aim: In several KT plans the researcher self evaluation is basis of researchers KT activities measurement so the aim of this study was the validity of researchers self assessment about their own activities in KT. Materials and Methods: The valid and reliable questionnaire was filled by 40 Golestan University of Medical Sciences researchers. In this questionnaire researchers were asked to give a score from 0 to 10 for their own activities in KT in a finished special project. Statistical analysis was performed using pair T test and Pearson correlation coefficient. The linear regression was used for assessing the effect of influential factors on KT self evaluation and activity scores. Results: The mean score of researchers KT activity and self evaluation was 3.52 and 5.47 respectively which this difference was statistically significant (P<0.01). The correlation coefficient between researchers' activity and self evaluation score was 0.73 which is an indicator of good correlation. The influential factors on researchers' KT self evaluation score in regression model was male gender, having administrative responsibility and percent of total time allocated to research and the influential factors on researchers' KT activities score in regression model was male gender, type of research (clinical sciences research compared to basic sciences) and percent of total time allocated to research. Conclusion : The results of this study shows that researchers overestimate their own activities in KT so adopting strategies like education about KT concepts and activities for increasing researchers knowledge and perception can fill research and action gap.